COVID-19 Vaccine Hesitancy and Vaccination Status in a Community-Based Cohort of People Who Inject Drugs in Baltimore, Maryland, March–June 2021. (September 2022) - Cepeda, Javier A.; Feder, Kenneth A.; Astemborski, Jacqueline; Schluth, Catherine; Kirk, Gregory D.; Mehta, Shruti H.; Genberg, Becky L.
Objective: People who inject drugs are a population who are often unengaged with health care services. The objective of this study was to characterize COVID-19 vaccine hesitancy and uptake in a community-based sample of people who inject drugs in Baltimore, Maryland. Methods: The ALIVE study (AIDS Linked to the IntraVenous Experience) in Baltimore is a community-based cohort study of people with a history of injection drug use. From March 2 through June 28, 2021, 346 ALIVE participants completed a survey on substance use, structural determinants of health, and COVID-19 vaccine hesitancy. The exposure of interest was COVID-19 vaccine hesitancy, and the primary outcome was vaccination status as of June 30, 2021. We extracted data on the dates of vaccination from electronic medical records linked to study participants. Results: The median age of the sample was 60 years; most participants were male (66%) and non-Hispanic Black (87%). Most (55%) trusted the COVID-19 vaccine, and 68% had received ≥1 dose. After age standardization, survey participants were more likely than the Maryland general population to be unvaccinated (prevalence ratio = 1.20; 95% CI, 0.97-1.49; P = .10). Participants who somewhat trusted or did not trust the COVID-19 vaccine had 6-fold higher odds of being unvaccinated than participants who trusted the vaccine (odds ratio = 6.30; 95% CI, 3.74-10.60). Conclusion: Uptake of COVID-19 vaccine among people with a history of injection drug use was high. Attitudes and knowledge about vaccination were important predictors of vaccine uptake. Education and outreach efforts could be effective in reducing hesitancy and increasing vaccination in substance-using populations.